(3√28+√68)ab - √50ab+ (3√8+√18)ab - 2√175ab=
Ma ajutati va rog? :3
Răspunsuri la întrebare
Răspuns de
1
(3·2√7+2√17)ab- 5√2ab+ (3·2√2+3√2)ab - 2·5√7ab=6√7ab+2√17ab- 5√2ab+ 6√2ab+3√2ab - 10√7ab=2√17ab-3√7ab+4√2ab=ab(2√17-3√7+4√2)
Cynthi00:
Multumesc @Camytza2003 :*
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Chimie,
10 ani în urmă
Limba română,
10 ani în urmă
Engleza,
10 ani în urmă